THE EDUCATION SYSTEM IN INDONESIA: EMPOWERING TEACHERS FOR QUALITY EDUCATION IN THE REFORM ERA - Suriagiri; Fadloli; Shohib Muslim; Elmiwati; Muhammad Khoiri (International Journal of Teaching and Learning, 2023)
The Indonesian education system has undergone a profound transformation during the reform era that began in the late 1990s. This period of democratic change, economic shifts, and societal developments has reshaped the educational landscape in Indonesia. In this research, we explore the intricate evolution of the Indonesian education system during the reform era and emphasize the paramount importance of quality education. We argue that empowering teachers is instrumental in achieving this goal, positioning them at the core of meaningful educational reform. The shift from a centralized, rigid education system to a decentralized, adaptable one marked a seismic change in the Indonesian education system. The introduction of a competency-based curriculum aimed to equip students with essential skills, fostering critical thinking and problem-solving capabilities to prepare them for a dynamic global economy. Our research underscores the central role of teachers in shaping the quality of education and their pivotal position within the Indonesian education system. Empowering teachers becomes a fundamental prerequisite for the successful implementation of educational reforms. By investing in teachers, Indonesia can unlock its potential to create a more vibrant and dynamic education system, fostering enhanced student learning, ongoing professional development, and inclusivity.